The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1074/jbc.m110.146126
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-3B11, a Novel Vascular-type Laminin Capable of Inducing Prominent Lamellipodial Protrusions in Microvascular Endothelial Cells

Abstract: The basement membrane (BM) proteins laminins, which consist of ␣, ␤, and ␥ chains, support tissue structures and cellular functions. To date only ␣4 and ␣5 types of laminins have been identified in the BMs of blood vessels. Our recent study suggested the presence of novel ␣3B-containing laminins in vascular BMs. Here we identified and characterized the third member of vascular laminins, laminin-3B11 (Lm3B11). RT-PCR analysis showed that microvascular endothelial (MVE) cells and umbilical vein endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…In certain tissues, such as renal glomeruli, lung, and pancreatic islets, podocytes, alveolar epithelial cells, or islet β-cells, respectively, also rest on the subendothelial BM. The subendothelial BMs of most vessels contain two main laminin types, LM-511 and LM-411 (Hallmann et al 2005, Simon-Assmann et al 2011), but Mori et al (2010) recently identified a third less common isoform, LM-3B11, expressed by vascular endothelial cells. Strict developmental regulation of laminin expression appears to occur.…”
Section: Vascular Systemmentioning
confidence: 98%
“…In certain tissues, such as renal glomeruli, lung, and pancreatic islets, podocytes, alveolar epithelial cells, or islet β-cells, respectively, also rest on the subendothelial BM. The subendothelial BMs of most vessels contain two main laminin types, LM-511 and LM-411 (Hallmann et al 2005, Simon-Assmann et al 2011), but Mori et al (2010) recently identified a third less common isoform, LM-3B11, expressed by vascular endothelial cells. Strict developmental regulation of laminin expression appears to occur.…”
Section: Vascular Systemmentioning
confidence: 98%
“…22 Recently, laminin-3B11 (α 3B β 1 γ 1 , LM3B11) was identified as a novel vascular laminin predominantly expressed in capillaries and small veins. 23 The α 3B chain has the highest homology to α 5 , 23 but whether LM3B11 allows platelet adhesion remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…( 19 ) Furthermore, it was found that the laminin α3B chain is expressed as a novel laminin isoform, laminin‐3B11 (Lm3B11; α3B/β1/γ1), in vascular endothelial cells. ( 20 ) This new vascular laminin was expressed as a recombinant protein in HEK‐293 cells. Although the purified Lm3B11 showed moderate cell adhesion and motility activity toward epithelial cells, it strongly stimulated vascular endothelial cells to extend multiple protrusions, suggesting its involvement in the formation or maintenance of complex vascular network.…”
mentioning
confidence: 99%